CIHR Canadian HIV Trials Network Co-Infection and Concurrent Diseases Core: Updated Canadian Guidelines for the Treatment of Hepatitis C Infection in HIV-hepatitis C Coinfected Adults - Mark Hull; Stephen Shafran; Alice Tseng; Pierre Giguère; Marina B Klein; Curtis Cooper (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Hepatitis C virus (HCV) coinfection occurs in 20% to 30% of Canadians living with HIV and is responsible for a heavy burden of morbidity and mortality. Management of HIV-HCV coinfection is more complex due to the accelerated progression of liver disease, the timing and nature of antiretroviral and HCV therapy, mental health and addictions management, socioeconomic obstacles and drug-drug interactions between new HCV direct-acting antiviral therapies and antiretroviral regimens.